Harry Luke (ed Peter & Michael Luke): The Tenth Muse - A Gourmet’s Compendium - Davidson, Alan E (Petits Propos Culinaires, 1992)
Harry Luke (ed Peter & Michael Luke): The Tenth Muse - A Gourmet’s Compendium: Rubicon Press, London, 1992: 264 pp, b/w photographs, appendix on Saint Vita (patron saint of cooks), index, paperback,£ 12.95.